New Rethinking on Managers’ Competency Criteria and Success Factors in Airport Construction Projects - Alireza Roshani; Mohsen Gerami; Omid Rezaeifar (Salehan Institute of Higher Education, 2018)
The present research was conducted with the aim of rethinking the criteria competency of airport construction project managers. The research methodology was applied in terms of purpose, and a combination of descriptive survey methods and content analysis in terms of implementation. The statistical population consisted of 550 experienced managers of construction industry in public and private sectors, including contractors, consulting engineers and their employers in Iran in the late decade to 2017. The sample size was 230 according to Morgan sampling table. The subjects were collected by stratified purposeful sampling method. The data gathering tools were the managers' desirability questionnaire with a reliability coefficient of 0.916, a project success rate with a reliability coefficient of 0.863 and an interview with the managers with an agreement coefficient of 0.899. The data were analyzed by SPSS and TOPSIS software using descriptive statistics of frequency, percentage, mean, standard deviation, and inferential statistics of exploitation, Factor analysis, Kolmogorov-Smirnov Test, and one-way ANOVA. The results of the research indicated that the airport construction is of great importance due to the necessity of developing the infrastructure and the territorial location. The criteria of competencies for managers in the airport construction industry are different from the past and attention to local and environmental criteria is among the recognized management criteria. The priority of localized thirteen competencies of the project managers was leadership, project financing, project cost management, problem solving, project governance, time management, strategic management, quality management, controlling and integrated management, managing legislation and regulations, networking and professional ethics. Moreover, the local factors of the project success in priority order were timely allocation of funds, appropriate financial support, integration, upstream project management, appropriate financing of financial needs, management integration, strategic stability, stakeholder commitment and accountability, review cost mismatch, completion of the project in due time, increase of knowledge level in the organization.